Community Empowerment through Mentari Baitul Mal Wat Tamwil (BMT) to Boost Muslim Family Economy in Kotagajah Central Lampung - Nasor, M.; Ngisomuddin, Ngisomuddin; Alamsyah, Yosep Aspat (Jurnal Ilmiah Peuradeun, 2019)
An empowerment program is an activity that has the purpose of developing and improving the quality of life of the community in order to overcome the problems of their lives. Such conditions will provide a great opportunity for the community to improve capabilities in various fields including the economic field. All of these will have implications for improving and changing the capabilities of the abilities towards better progress. community towards better progress in shared life. The process of giving is not only done by the government, but also by social institutions such as the Mentari Baitul Mal Wat Tanwil (BMT) Kotagajah Central Lampung, the object of it is the empowerment of Muslim family traders. The Empowerment carried out by Mentari BMT as a financial institution refers to the financial screening system given to Muslim family traders. The financial screening is used for financing as an effort to improve the economy of the community. An Empowerment is an activity that can develop and improve the quality of life of traders of Muslim families who are independent and can overcome the problems of their lives. All of these have implications for their improvement and change.